Selective Inhibitor Detector of Ge-Doped Al-Mg Surface: Molecular Modeling Approach using DFT & TD-DFT Calculations - (:unkn) unknown (AMG Transcend Association, 2024)
The infrared spectra for each of these inhibitor-metal alloy surfaces have been introduced in the frequency range around 500 cm-1-3500 cm-1 for benzotriazole→Al-Mg-Ge, 2-mercaptobenzothiazole → Al-Mg-Ge, and 8- hydroxyquinoline → Al-Mg-Ge; 500-4000 for 3-amino-1, 2, 4-triazole-5-thiol → Al-Mg-Ge with the sharpest peak approximately around 2000 cm-1, 3000 cm-1 for benzotriazole → Al-Mg-Ge, 2-mercaptobenzothiazole→Al-Mg-Ge, and 8- hydroxyquinoline → Al-Mg-Ge; 2000 cm-1, 4000 cm-1 for 3-amino-1, 2, 4-triazole-5-thiol → Al-Mg-Ge. Nuclear magnetic resonance has focused on the intra-atomic and interatomic interactions through a variety of high, medium, and low layers of the ONIOM method. Al-Ge(14), Al-Ge(19), and Al-Ge(21) in the Al-Mg-Ge alloy surface with the highest fluctuation in the shielding tensors of the NMR spectrum generated by intra-atomic interaction direct us to the most influence in the neighbor atoms generated by interatomic reactions of N→Al, O→ Al, S→ Al through the coating and adsorbing process of Langmuir adsorption.